Effects Of Youtube Tutorial On Mental Computation Competency Of Pre-Service Teachers - Zulkifli Zulkifli; Yuhasriati Yuhasriati; Nida Jarmita; Zaid Zainal; Jasmaniah Jasmaniah; Samsul Bahri (UNIVERSITAS SERAMBI MEKKAH, 2022)
AbstractThis study aims at investigating the effect of youtube tutorial on mental computation flexibility among pre-service teachers. Mental computation might be vied as a relatively new term among students and teachers. Therefore, to introduce it to them need various methods and approaches. This study provided extra online material posted in youtube as a learning resource for pre-service primary teachers. The method used in this study was the pre-experimental research with the type of one-group pretest-posttest design. The population of this study was Indonesian pre-service teachers and the sample was chosen by technique of purposive sampling. The sample was from four universities in Indonesian, three public universities and one private university. The data were collected and analyzed both quantitatively and qualitatively. The quantitative approaches used this study were wilcoxon test and N-gain value. The result of the study showed that youtube tutorials have a significance impact on the improvement pre-service teachers’ competency of mental computation.